Homo‐ and Heteroleptic Phototoxic Dinuclear Metallo‐Intercalators Based on RuII(dppn) Intercalating Moieties: Synthesis, Optical, and Biological Studies. Issue 41 (7th September 2017) - Saeed, Hiwa K.; Jarman, Paul J.; Archer, Stuart; Sreedharan, Sreejesh; Saeed, Ibrahim Q.; Mckenzie, Luke K.; Weinstein, Julia A.; Buurma, Niklaas J.; Smythe, Carl G. W.; Thomas, Jim A.
Abstract: Using a new mononuclear "building block, " for the first time, a dinuclear Ru II (dppn) complex and a heteroleptic system containing both Ru II (dppz) and Ru II (dppn) moieties are reported. The complexes, including the mixed dppz/dppn system, are 1 O2 sensitizers. However, unlike the homoleptic dppn systems, the mixed dppz/dppn complex also displays a luminescence "switch on" DNA light‐switch effect. In both cisplatin sensitive and resistant human ovarian carcinoma lines the dinuclear complexes show enhanced uptake compared to their mononuclear analogue. Thanks to a favorable combination of singlet oxygen generation and cellular uptake properties all three of the new complexes are phototoxic and display potent activity against chemotherapeutically resistant cells. Abstract : 2 for 1 on PDT : New dinuclear Ru II (dppn) and mixed Ru II (dppn)/Ru II (dppz) complexes display much enhanced cellular uptake properties compared to simple Ru II (dppz) analogues. They are phototoxic and are particularly potent against chemotherapeutically resistant cells. The luminescent Ru II (dppn)/Ru II (dppz) complex also offers potential as a theranostic lead.